INTRODUCTION TO HOTEL OPERATION FOR STUDENTS OF SMK NEGERI 7 CITY OF TANGERANG - Rahmat Kusnedi; Nova Bernedeta Sitorus; Budi Setiawan; Dede Fahruroji; Johann Prawiro (STKIP PGRI SITUBONDO, 2022)
The hotel is in the lodging operations section where the main activity is to rent comfortable and safe rooms to guests. The level of service offered in a hotel starts from the core benefit, namely a room to stay. Core benefits are supported by facilitating service or often referred to as hotel operations such as front office, housekeeping, food and beverage, and kitchen/pastry. Vocational High Schools are expected to be able to become quality resources, they are not only taught theoretical classes but are also taught skills according to what is needed by the industry. Therefore, the Community Service Team of the Pradita University Tourism Study Program would like to share knowledge about hotel operations with partners, in this case, SMK Negeri 7 Tangerang City. This activity will begin with an introduction to the campus and after that the participants are divided into VHP practice and kitchen practice. To measure the extent to which participants understand the material that has been made, a pre-test and post-test will be conducted. This activity is guided by lecturers who are experts in the front office and kitchen, assisted by several students. Participants who take part in practical activities using the VHP software gain increased knowledge and can make reservations about the software. Participants who take part in cooking practice activities can make Indonesian dishes such as grilled konro and tekwan soup.